2016
DOI: 10.1155/2016/9150819
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D Effects on Osteoblastic Differentiation of Mesenchymal Stem Cells from Dental Tissues

Abstract: 1α,25-Dihydroxyvitamin D3 (1,25(OH)2D3), the active metabolite of vitamin D (Vit D), increases intestinal absorption of calcium and phosphate, maintaining a correct balance of bone remodeling. Vit D has an anabolic effect on the skeletal system and is key in promoting osteoblastic differentiation of human Mesenchymal Stem Cells (hMSCs) from bone marrow. MSCs can be also isolated from the immature form of the tooth, the dental bud: Dental Bud Stem Cells (DBSCs) are adult stem cells that can effectively undergo … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
49
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(55 citation statements)
references
References 48 publications
4
49
0
1
Order By: Relevance
“…However, a recent pilot study in mechanically ventilated ICU patients showed that high dose of vitamin D3 was associated with decreased hospital length of stay, but no statically significant change in plasma LL-37 concentrations or other clinical outcomes (181). While the stimulatory effect of Vitamin D has been described for the osteogenic potential of MSCs (182), future experiments are required to address their effect on the expression of AMPs both in vitro and in vivo . This could represent an alternative approach by stimulating the endogenous MSCs to secrete higher amount of AMPs.…”
Section: Trends Future Perspectives and Challengesmentioning
confidence: 99%
“…However, a recent pilot study in mechanically ventilated ICU patients showed that high dose of vitamin D3 was associated with decreased hospital length of stay, but no statically significant change in plasma LL-37 concentrations or other clinical outcomes (181). While the stimulatory effect of Vitamin D has been described for the osteogenic potential of MSCs (182), future experiments are required to address their effect on the expression of AMPs both in vitro and in vivo . This could represent an alternative approach by stimulating the endogenous MSCs to secrete higher amount of AMPs.…”
Section: Trends Future Perspectives and Challengesmentioning
confidence: 99%
“…Vitamin D is essential for normal bone formation and mineralization, and plays a critical role in bone biology . Disordered vitamin D metabolism plays a crucial role in SHPT along with other changes of mineral metabolism.…”
Section: Vitamin D Deficiency‐related Bone Quantity Lossmentioning
confidence: 99%
“…Vitamin D is essential for normal bone formation and mineralization, and plays a critical role in bone biology. 91,92 Disordered vitamin D metabolism plays a crucial role in SHPT along with other changes of mineral metabolism. Vitamin D deficiency is common in advanced CKD, and the BMD is positively correlated with the serum 25(OH)D concentration.…”
Section: Vitamin D Deficiency-related Bone Quantity Lossmentioning
confidence: 99%
“…Although the main known source of MSCs is the bone marrow, a wide variety of MSCs have been recognized in dental tissues such as pulp, periodontal ligament and apical papilla, exhibiting several multilineage potencies including osteogenic, adipogenic and neurogenic (24)(25)(26)(27)(28)(29)(30), besides the expected odontogenic (31). In our previous studies, we demonstrated the stem cell properties of dental tissues such as pulp, follicle and bud, as well as their ability to differentiate into osteoblasts (32)(33)(34)(35)(36)(37)(38). According to our findings, differentiated dental pulp stem cells (DPSCs) express high levels of TRAIL.…”
Section: Introductionmentioning
confidence: 57%